Alexandria, Kom el-Dikka, season 2021 - Grzegorz Majcherek (Polish Archaeology in the Mediterranean, 2022)
Excavations of the central part of the Kom el-Dikka archaeological site in Alexandria have reached early Roman levels and the current investigations of the PCMA UW expedition are focused on completing the excavation of some of the partly uncovered architecture. The southwestern part of House FA was explored, uncovering two fragments of colourful mosaic floors. Building chronology was established based on finds from two deep stratigraphic probes dug inside the structure. The main phases of occupation of House FA turned out to be comprised in a period between the 1st and 3rd centuries CE. The archaeological part of the program was accompanied by current preservation and maintenance work that the team is tasked with in different parts of the site; necessary preservation projects were undertaken this year in the theatre, the portico in front of the theatre and the early Roman buildings in the central part of the site. The mosaics on display in the mosaic shelter have also undergone cyclical conservation treatment.